The portrayal of gender difference toward swear word: an investigation of words and expressions used by Indonesian students - Siti Aisyah; Chairuddin Chairuddin; Tera Athena (Universitas Islam Malang, 2020)
The society in using language is susceptible to any type of word including the expression of swear word. This research aims to determine of the types in swear word use based on the gender of its use in communication. Descriptive qualitative is used as a research approach and its application uses phenomenology methods. The data are from male and female students by matching them to Wardhaugh’s and Jay’s list of swear word. Students of elefth social three are selected for this research. Analysis of the results of gender-based reviews shows that men are stronger in the use of swear word forms. In contrast to women who are more aggressive and talk much only in their groups. Sex, death, excretion, bodily functions, religious matters, politics, mother-in-law, animals, nicknames are more widely used by men. For the types of rude comments women use more. This is indicated by their words and expressions that are more feminine and long-winded. Finally, the swear word which is included in this taboo word is used sometimes not the same for men and women.